Son of a Lesser God: The Case of Cell Therapy for Refractory Angina - Bassetti, Beatrice; Rurali, Erica; Gambini, Elisa; Pompilio, Giulio (Frontiers in Cardiovascular Medicine, 2021)
In the last decades, various non-pharmacological solutions have been tested on top of medical therapy for the treatment of patients affected by refractory angina (RA). Among these therapeutics, neuromodulation, external counter-pulsation and coronary sinus constriction have been recently introduced in the guidelines for the management of RA in United States and Europe. Notably and paradoxically, although a consistent body of evidence has proposed cell-based therapies (CT) as safe and salutary for RA outcome, CT has not been conversely incorporated into current international guidelines yet. As a matter of fact, published randomized controlled trials (RCT) and meta-analyses (MTA) cumulatively indicated that CT can effectively increase perfusion, physical function and well-being, thus reducing angina symptoms and drug assumption in RA patients. In this review, we (i) provide an updated overview of novel non-pharmacological therapeutics included in current guidelines for the management of patients with RA, (ii) discuss the Level of Evidence stemmed from available clinical trials for each recommended treatment, and (iii) focus on evidence-based CT application for the management of RA.